Understanding products as services : how the internet and AI are transforming product companies - Wortmann, Felix; Gebauer, Heiko; Lamprecht, Claudio; Fleisch, Elgar (Emerald Publishing Limited, 2024)
In the realm of global commerce, Europe has long been renowned for its exceptional hardware products, dominating markets with its machine tools and luxury automobiles. However, it has lost the Internet game and consumes almost all Internet services from the USA and has China on the rise in all dimensions. However, with the emergence of the Internet of Things, the convergence of hardware-based products with software-based services offers a new avenue for success. Understanding Products as Services discusses how to succeed in the emerging hybrid economy, in which the term 'hybrid' represents the mixture of digital and physical products and services that is required to offer a state-of-the-art customer experience. The authors do not rely on lofty concepts but propose tangible and validated tools. Whether you are an industry professional, an entrepreneur, a business student, or a researcher, Understanding Products as Services serves as an indispensable guide for navigating the hybrid economy, enabling you to leverage the integration of hardware and software, and propel your organization to the forefront of innovation and success.